Manganese dioxide mediated one-pot synthesis of methyl 9H-pyrido[3,4-b]indole-1-carboxylate: Concise synthesis of alangiobussinine - Baiget, Jessica; Llona-Minguez, Sabin; Lang, Stuart; MacKay, Simon P.; Suckling, Colin J.; Sutcliffe, Oliver B. (Beilstein Journal of Organic Chemistry, 2011)
The carboline ring system is an important pharmacophore found in a number of biologically important targets. Development of synthetic routes for the preparation of these compounds is important in order to prepare a range of analogues containing the carboline heterocyclic moiety. A manganese dioxide mediated one-pot method starting with an activated alcohol and consisting of alcohol oxidation, Pictet–Spengler cyclisation, and oxidative aromatisation, offers a convenient process that allows access to β-carbolines. This one-pot process for the preparation of methyl 9H-pyrido[3,4-b]indole-1-carboxylate has subsequently been used as the key step in the synthesis of alangiobussinine and a closely related analogue.
Keywords: alkaloid synthesis; carboline; heterocycle; oxidation; tandem reaction